Effects of a Bacillus-based spore probiotic on the gut microbiota of weaned piglets - Olena Kolchyk; Sergii Borovkov; Oleksandr Tarasov; Anatoliy Paliy; Polina Yurko; Oleksandr Akimov; Nadiya Selishcheva; Tetiana Tykhomyrova; Oleksandr Tsereniuk; Anatoliy Korobka; Vitalii Vovk; Svitlana Lobchenko (Universitas Airlangga, 2026)
The post-weaning period is one of the most critical stages in piglet development, often associated with metabolic disorders that negatively affect weight gain and product quality. To support gastrointestinal microbiocenosis, transient spore-forming bacteria of the genus Bacillus are commonly used as probiotics. In this study, 20 clinically healthy Large White piglets, aged 28 days and recently weaned, received an orally administered spore probiotic mixed into their feed for three weeks. Fecal samples were collected before and after treatment, and microbial community composition was analyzed using 16S rRNA gene sequencing. Paired statistical tests assessed alpha-diversity (paired Wilcoxon) and beta-diversity (Bray–Curtis, PERMANOVA). Following supplementation, median reductions in the relative abundance of the phyla Bacillota, Bacteroidota, and Pseudomonadota were approximately 3–5%, while several low-abundance phyla (e.g., Actinobacteriota, Verrucomicrobiota, Fibrobacteriota) increased by about 1–2%. The spore probiotic decreased dominant microbiota proportions while enhancing less common but beneficial taxa, maintaining stable diversity and contributing to improved metabolism and microbial balance in the piglets’ intestines. Its antagonistic properties also help protect piglets from infections and inhibit pathogenic bacterial development.